Prevalence and correlates of dating violence among Mexican Adolescent and Youth Women - Rodríguez Hernández, Rogelio; Castillo-Viveros, Nemesio; Esquivel-Santoveña, Esteban Eugenio (Psychology, Society & Education, 2023)
The purpose of this study was to know the prevalence and correlates of recent emotional, physical, and sexual violence experienced in dating relationships among a representative national sample of 15 to 24-year-old single Mexican women (n = 7,140; Mage = 19.3; SD = 2.7). The source of information was the National Survey on the Dynamics of Relationships in Households 2021 (ENDIREH-2021) and an ecological framework, and a conflict perspective were used to organize and interpret the information. It was found that 16.32%, 2.66% and 2% of the participants had suffered emotional, physical, and sexual violence, respectively, in a dating relationship during the last year. Factors that increased the risk of dating violence were disability condition, violence in childhood, recent violence by the family, time with the partner, employment, and social participation. Variables that protected from abuse were school years, and attitudes toward equality among men and women. These findings have implications for policies aimed at ending preventing dating violence.